Unique mouse monoclonal antibodies reactive with maturation‐related epitopes on type VII collagen. Issue 9 (20th April 2017) - Hayakawa, Taihei; Hirako, Yoshiaki; Teye, Kwesi; Tsuchisaka, Atsunari; Koga, Hiroshi; Ishii, Norito; Karashima, Tadashi; Kaneda, Minori; Oyu, Yuka; Tateishi, Chiharu; Sugawara, Koji; Yonamine, Ayano; et al.
Abstract: In this study, we generated a new set of monoclonal antibodies (mAbs) to bovine and human type VII collagen (COL7) by immunizing mice with bovine cornea‐derived basement membrane zone (BMZ) fraction. The four mAbs, tentatively named as COL7‐like mAbs, showed speckled subepidermal staining in addition to linear BMZ staining of normal human skin and bovine cornea, a characteristic immunofluorescence feature of COL7, but showed no reactivity with COL7 by in vitro biochemical analyses. Taking advantage of the phenomenon that COL7‐like mAbs did not react with mouse BMZ, we compared immunofluorescence reactivity between wild‐type and COL7‐rescued humanized mice and found that COL7‐like mAbs reacted with BMZ of COL7‐rescued humanized mice. In ELISAs, COL7‐like mAbs reacted with intact triple‐helical mammalian recombinant protein (RP) of COL7 but not with bacterial RP. Furthermore, COL7‐like mAbs did not react with COL7 within either cultured DJM‐1 cells or basal cells of skin of a bullous dermolysis of the newborn patient. These results confirmed that COL7‐like mAbs reacted with human and bovine COL7. The epitopes for COL7‐like mAbs were considered to be present only on mature COL7 after secretion from keratinocytes and deposition to BMZ and to be easily destroyed during immunoblotting procedure. Additional studies indicated association of the speckled subepidermal staining with both type IV collagen and elastin. These unique anti‐COL7 mAbs should be useful in studies of both normal and diseased conditions, particularly dystrophic epidermolysis bullosa, which produces only immature COL7.